Diagnosis and management of hypertension in primary care. Issue 4 (18th April 2019) - Pucci, Mark
Abstract : Hypertension is a major modifiable risk factor for cardiovascular disease, but conflicting opinions remain about optimal blood pressure targets. This article discusses the various definitions of hypertension, provides guidance on management in primary care and advises when referral to secondary care is needed.